The Taliban, Islam and Women's Rights in the Muslim World - Levitt, Matthew A. (Tufts Archival Research Center, 2005)
Volume 22, Issue 1. Winter/Spring Events in Afghanistan and the Taliban militia's enforcement of strict Shari'a law, and restrictions on women's activities have sparked interest in the different approaches to Islamic interpretation in the Muslim world.